Conference on challenges in sarcoma (CCS) 2024: expert opinions on non-evidence-based management aspects - Hofer, Silvia; Pauli, Chantal; Bode, Beata; Bonvalot, Sylvie; Fotopoulou, Christina; Gelderblom, Hans; Haas, Rick L; Hardes, Jendrik; Hohenberger, Peter; Jakob, Jens; Kunz, Wolfgang G.; Leithner, Andreas; et al. (European journal of cancer, 2025)
Background - Soft tissue sarcomas (STS) and other mesenchymal tumours belong to rare, heterogeneous neoplasms with over 150 subtypes that pose significant challenges in diagnosis and clinical decision making. While guidelines address evidence-based diagnostic and therapeutic procedures, clinical situations and scenarios without evidence remain controversial in daily practice. The 2024 Conference on Challenges in Sarcoma (CCS2024) aimed to narrow these gaps with the support of an international and multidisciplinary panel of sarcoma experts. - Methods - A Delphi process identified 200 controversial questions across eight prioritised clinical scenarios, including tenosynovial giant cell tumour, synovial sarcoma of the extremities, retroperitoneal sarcomas, angiosarcoma, phyllodes tumour, malignant peripheral nerve sheath tumour, uterine leiomyosarcoma, and atypical lipomatous tumour. - Results - Sixty-four experts discussed 141 controversies during the conference and reached strong consensus (> 90%) on 24 and consensus (> 75%) on 45 key diagnostic and therapeutic issues, while unresolved controversies emphasized the need for further research. - Conclusions - CCS2024 provides a framework for clinical decision making and underscores the importance of consensus-driven approaches in the treatment of rare and complex malignancies.
Online verfügbar: 17. März 2025, Artikelversion: 4. April 2025
Gesehen am 04.06.2025